STUDI MENURUNNYA JUMLAH WISATAWAN YANG BERKUNJUNG DI TAMAN BUMI KEDATON - Widiya Wati; Edy Haryono; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2013)
The objective of this research is to get the information about the decreasing of the number of tourist who visits Bumi Kedaton Park in Batu Putu village of north Teluk Betung regency of Bandar Lampung city in 2011, with point of the investigation in the attractiveness of the tourist object, accessibility, facility, security, publication and promotion.The method that was used in this research was descriptive research method. The population of this research was the tourist who visits Bumi Kedaton Park, used quota technique sampling, and the number of respondent were 60 respondents. In collecting the data, the researcher used observation, interview, questionnaire and documentation. In analyzing the data, the researcher used percentage technique and scoring with the pattern of Struges Model as the basic description of making this research.Based on the result of this research, it can be concluded that: 1) The condition of the tourist object of Bumi Kedaton Park is interesting enough, it was proved by the 17 score. So it is not the factor that affected of decreasing the number of tourist who visits. 2) The accessibility to reach Bumi Kedaton Park is medium, it was proved by the 18 score, so it is not the factor that affected of decreasing the number of tourist who visits. 3) The facility in the tourist object of Bumi Kedaton Park is not suitable with the tourist requirement, it was proved by the 19 score, so it is not the factor that affected of decreasing the number of tourist who visits. 4) The condition of the security in Bumi Kedaton Park is secure, it was proved by the 13 score, so it is not the factor that affected of decreasing the number of tourist who visits. 5) Promotion and publication of Bumi Kedaton Park is not good, it is proved by the 7 score, so it is the factor that affected the decreasing of the number of tourist who visited.Key Word: The condition of the tourist object, The accessibility, The facility, The condition of the security, Promotion and publication